Advanced player tracking system - Ales Skerbinek; Bostjan Vlaovic (Institute of Advanced Engineering and Science, 2019)
The Player Tracking System (PTS) is already well renowned in the Casino industry. It can track the activity of users and monitor the performance and operation of gaming machines. The recognized downside of such a system is that users usually do not want to be tracked, mostly, because they feel that the functioning of the gaming machine might be tampered with to minimize their winning potential. PTS has to offer a variety of services to stimulate a user to use the membership card. In this paper, we propose an Advanced PTS that simplifies some tedious tasks, automates conversion of bonus points to playing credits, displays jackpot counters, introduces the gaming machine reservation system, provides cashless transfers, delivers interactive personalized awards and promotions with prize winning games, enables ordering of refreshments from the gaming machine, and provides some additional innovative features. Its use reduces the workload of casino employees and enables the casino management team to access configuration of the system and analytical data with the use of a web browser from all desired locations and devices. The biggest installation of the presented APTS manages more than 400 gaming machines, and is well-received by the users.